Lubiprostone targets prostanoid signaling and promotes ion transporter trafficking, mucus exocytosis and contractility - Jakab, Robert L. (2012)
BACKGROUND AND AIM: Lubiprostone is a chloride channel activator in clinical use for the treatment of chronic constipation, but the mechanisms of action of the drug are poorly understood. The aim of this study was to determine whether lubiprostone exerts secretory effects in the intestine by membrane trafficking of ion transporters and associated machinery. METHODS: Immunolabeling and quantitative fluorescence intensity were used to examine lubiprostone-induced trafficking of the cystic fibrosis transmembrane conductance regulator (CFTR), sodium/potassium-coupled chloride co-transporter 1 (NKCC1), electrogenic sodium/bicarbonate co-transporter 1 (NBCe1), down-regulated in adenoma (DRA), putative anion transporter 1 (PAT1), sodium/proton exchanger 3 (NHE3), Ca(2+) activated chloride channel 2 (ClC-2) serotonin and its transporter SERT, E prostanoid receptors EP4 and EP1, sodium/potassium ATPase (Na-K-ATPase) and protein kinase A (PKA). The effects of lubiprostone on mucus exocytosis in rat intestine and human rectosigmoid explants were also examined. RESULTS: Lubiprostone induced contraction of villi and proximal colonic plicae and membrane trafficking of transporters that was more pronounced in villus/surface cells compared to the crypt. Membrane trafficking was determined by: (1) increased membrane labeling for CFTR, PAT1, NKCC1, and NBCe1 and decreased membrane labeling for NHE3, DRA and ClC-2; (2) increased serotonin, SERT, EP4, EP1 and PKA labeling in enterochromaffin cells; (3) increased SERT, EP4, EP1, PKA and Na-K-ATPase in enterocytes; (4) and increased mucus exocytosis in goblet cells. CONCLUSION: These data suggest that lubiprostone can target serotonergic, EP4/PKA and EP1 signaling in surface/villus regions; stimulate membrane trafficking of CFTR/NBCe1/NKCC1 in villus epithelia and PAT1/NBCe1/NKCC1 in colonic surface epithelia; suppress NHE3/DRA trafficking and fluid absorption; enhance mucus-mobilization and mucosal contractility.